Analisa Penentuan Water Vapor Terhadap Pengaruh Erupsi Gunung Sinabung Menggunakan Data SUGAR Dan Citra Satelit Terra MODISs - Safridatul Audah; Mokhamad Nur Cahyadi; Muhammad Taufik (Jurnal Inotera, 2017)
The eruption of Mount Sinabung in 2010 caused bursts of volcanic ash particles into the atmosphere layer to impact the weather. This is because volcanic ash is hydrocopic which can cause condensation process and block the process of solar radiation earth surface. Precivitable Water vapor (PWV) as one of the parameters of the atmosphere that can be used as information to determine the weather conditions in an area. Utilization of data Sumatran GPS Array (SUGAR) and data satellite Terra sensors MODIS (Moderate Resolution Imaging Spektroradiometer) can be used to find out PWV through GPS inversion method by utilizing estimated estimation of slowing and rotating GPS signals overlaid with troposphere. While the transmittance method is performed by comparing the surface reflectance between the channel absorption and the channel non absorption contained in the sensor MODIS. The results showed that spatial variation of PWV distribution pattern showed wetness pattern during eruption. This was indicated by some areas that have PWV distribution pattern almost in each region and PWV verification result from GPS showed ± 47.65 mm-66.81 mm, while PWV value from MODIS ranges from ± 13.02 mm - 80.05 mm. Based on the results of PWV-GPS correlation test from June to October of 2010 has a correlation coefficient of 0.0173 to PWV from MODIS and explains the positive relationship between PWV of GPS with PWV value from MODIS, but correlation value of the variable variables including low category because of location points Station SUGAR are spread unevenly and are more likely to spread along the western coast of Sumatra, which borders the Indian Ocean.